Visible-Light-Driven Photocatalytic Water Disinfection Toward Escherichia coli by Nanowired g-C3N4 Film - Zhang, Yizhu; Su, Shigang; Zhang, Yuanyuan; Zhang, Xia; Giusto, Paolo; Huang, Xiaohua; Liu, Jian (Frontiers in Nanotechnology, 2021)
Graphitic carbon nitride (g-C3N4) as metal-free visible light photocatalyst has recently emerged as a promising candidate for water disinfection. Herein, a nanowire-rich superhydrophilic g-C3N4 film was prepared by a vapor-assisted confined deposition method. With a disinfection efficiency of over 99.99% in 4 hours under visible light irradiation, this nanowire-rich g-C3N4 film was found to perform better than conventional g-C3N4 film. Control experiments showed that the disinfection performance of the g-C3N4 film reduced significantly after hydrophobic treatment. The potential disinfection mechanism was investigated through scavenger-quenching experiments, which indicate that H2O2 was the main active specie and played an important role in bacteria inactivation. Due to the metal-free composition and excellent performance, photocatalytic disinfection by nanowire-rich g-C3N4 film would be a promising and cost-effective way for safe drinking water production.